SURVEY AND SUMMARY: The applications of universal DNA base analogues - Loakes, David (Oxford University Press, 2001)
A universal base analogue forms ‘base pairs’ with each of the natural DNA/RNA bases with little discrimination between them. A number of such analogues have been prepared and their applications as biochemical tools investigated. Most of these analogues are non-hydrogen bonding, hydrophobic, aromatic ‘bases’ which stabilise duplex DNA by stacking interactions. This review of the literature of universal bases (to 2000) details the analogues investigated, and their uses and limitations are discussed.